A Community-Based Needs Assessment of Resettled Syrian Refugee Children and Families in Canada - Al-Janaideh, Redab; Abdulkarim, Maarya; Speidel, Ruth; Filippelli, Joanne; Colasante, Tyler; Malti, Tina (Refuge: Canada's Journal on Refugees, 2023)
A needs assessment was conducted to identify the needs, challenges, and strengths of Syrian refugee children and families resettled in Canada and of services for these refugees. Ten refugee caregivers and 17 service providers were interviewed. Thematic analyses indicated significant needs and challenges experienced by refugees (e.g., persistent mental health issues, lack of in-person support), as well as challenges related to refugee services (e.g., discontinuity of mental health services). Several refugee strengths (e.g., optimism for the future and strong familial ties) and refugee service strengths (e.g., service collaboration) were identified, highlighting refugees’ adaptive capacities and points of service leverage to ensure refugees’ well-being and positive resettlement.